Biodiesel production from waste cooking oil using a novel heterogeneous catalyst based on graphene oxide doped metal oxide nanoparticles. (December 2020) - Jume, Binta Hadi; Gabris, Mohammad Ali; Rashidi Nodeh, Hamid; Rezania, Shahabaldin; Cho, Jinwoo
Abstract: Waste cooking oil (WCO) is a potential and low-cost source for biodiesel production which has been used widely. In this study, novel nanocatalyst (GO@ZrO2 –SrO) was synthesized via co-precipitation method by the combination of both potential graphene oxide and bimetal zirconium/strontium oxide nanoparticles. The proposed nanocomposite showed a promising ability as a heterogeneous catalyst for the transesterification of WCO to produce FAMEs as biodiesel. The FTIR, SEM/EDX and XRD were used for the characterization of nanocatalyst to evaluate the surface functional groups, nanostructure/elements and crystallinity, respectively. The effective parameters on the transesterification FAMEs yield including oil to alcohol ratio, reaction time, and reaction temperature were studied. Based on the results, the maximum FAMEs yield of 91% was obtained in the conditions of the material ratio of 1:0.5 (w/w) of GO:ZrO2 –SrO, oil to methanol ratio (1:4), the reaction time of 90 min and the temperature of 120 °C. Therefore, this study showed that GO@ZrO2 –SrO can be used as an alternative potential heterogeneous catalyst to produce biodiesel from WCO. Highlights: Biodiesel production from graphene oxide doped metal oxide nanoparticles catalyst. The nanocatalyst was validated and characterized with FTIR, SEM/EDX and XRD. The catalyst ability reduced after fourth run due to the loss of active sites. The maximum biodiesel yield of 91% was obtained.